SEAKER cells coordinate cellular immunotherapy with localized chemotherapy. (October 2022) - Lane, Isabel C.; Jan, Max
Abstract : Tumor antigen escape and T cell dysfunction limit the effectiveness of chimeric antigen receptor (CAR) T cell therapies. To overcome these challenges, Gardner et al. engineered synthetic enzyme-armed killer (SEAKER) cells to coexpress a CAR and a prodrug-activating enzyme to orchestrate a dual immunologic and pharmacologic attack at the tumor site.